On Suárez's ethics: the fundamentals and effects = (Sobre la ética de Suárez) : (fundamentos y proyecciones) - Senent de Frutos, Juan Antonio; Viñas Vera, Ángel (Jesuit studies, 2026)
"Why revisit Suárez's moral thought today? This book offers the first integrated exploration of Francisco Suárez's ethical framework, combining unpublished sources, new critical editions, and fresh interpretations. With contributions in Spanish and English from leading scholars across Europe and the Americas, it examines the foundational structure and wide-reaching implications-social, political, legal, and religious-of Suárez's ethics. You'll discover a humanist and Jesuit thinker at the crossroads of medieval tradition and modern innovation. Engaging his neglected moral treatises and manuscripts, this volume opens a crucial window into early modern scholasticism and proposes Suárez as a key voice in shaping alternative models of modernity. ¿Por qué volver hoy al pensamiento moral de Suárez? Este libro ofrece la primera exploración integral del marco ético de Francisco Suárez, combinando fuentes inéditas, nuevas ediciones críticas y lecturas renovadas. Con contribuciones en español e inglés de destacados investigadores de Europa y América, analiza la estructura fundamental y las amplias implicaciones -sociales, políticas, jurídicas y religiosas- de su ética. Descubrirás a un pensador humanista y jesuita en la encrucijada entre la tradición medieval y la innovación moderna. Al abordar sus tratados morales menos atendidos y manuscritos inéditos, este volumen abre una ventana clave al pensamiento escolástico moderno y propone a Suárez como una voz central en modelos alternativos de modernidad"-- Provided by publisher